Improving health outcomes: innovation, coverage, quality and adherence - McKee Martin; Chow Clara K (BMC, 2012)
Abstract The Israeli health system has made considerable progress in reducing deaths amenable to medical care but has more to do. This commentary describes how progress in this area results from innovation, coverage, quality, and adherence to treatment. It describes what is being done in Israel and beyond to address each of these factors but concentrates on the often poorly recognised problem of adherence to treatment, describing the growing evidence that it is often sub-optimal and reviewing evidence on what can be done to improve it.